Association of endothelial nitric oxide synthase (NOS3) rs2070744 variant with advanced retinopathy of prematurity: a case–control study and meta-analysis - Aneta Choręziak-Michalak; Dawid Szpecht; Tomasz Woźniak; Anna Chmielarz-Czarnocińska; Patrycja Gazińska; Anna Gotz-Więckowska; Ewa Strauss (Scientific Reports)
Abstract Despite advances in neonatal and ophthalmological care, retinopathy of prematurity (ROP) continues to be a leading cause of childhood blindness worldwide. Investigating gene variants associated with vascular responses in ROP may provide valuable insights into its pathogenesis and identify risk or protective factors. Nitric oxide (NO) and endothelin-1 (ET-1) play roles in vascular regulation, influencing processes relevant to ROP development. Functional variants of genes encoding endothelial NO sythetase (NOS3 rs1799983, rs2070744), endothelin-1 (EDN1 rs5370), and endothelin receptor A (EDNRA rs5335) may influence ROP development or progression. The results of our study support the role of the rs2070744 variant in ROP. We identified the protective effect of the rs2070744C allele against the development of ROP requiring treatment, also after adjusting for covariates. Meta-analysis including 298 patients and 397 controls confirmed this protective role. The rs2070744CC homozygous genotype exhibited an odds ratio (OR) of 0.42 (adjusted P = 0.036). Additional meta-analysis results for NOS3 rs1799983 are presented, suggesting potential risk in a recessive model. No associations were found between EDN1, EDNRA variants, and ROP. Exploring genetic predispositions in ROP, including vascular regulation genes, can lead to personalized prevention and treatment approaches. Our results need to be replicated in a larger sample of premature infants.